Price discrimination, regulation and entry in the UK residential electricity market (2001)
The residential electricity market in Great Britain has recently been opened to competition and is served by 14 regional incumbents, and up to 15 entrants in each area. This study finds that the incumbents' regulated prices are discriminatory between consumers using different payment methods, and that firms are practising third-degree price discrimination between areas. The authors discuss the implications for regulatory policy both in the UK and in other countries where electricity markets are being deregulated.